A case of discrepancy between three ERA tests in a woman with repeated implantation failure complicated by chronic endometritis - Kuniaki Ota; Toshifumi Takahashi; Junichiro Mitsui; Kishio Kuroda; Kenichiro Hiraoka; Kiyotaka Kawai (BMC, 2022)
Abstract Background Endometrial receptivity array (ERA) is used to determine the timing of embryo transfer (ET) synchronized with the window of implantation (WOI). The effectiveness and evaluation of ERAs in women with recurrent implantation failure remain controversial. We report the case of a patient with recurrent implantation failure that raises the issue of reproducibility of ERA tests. Case report A 36-year-old Japanese woman with secondary infertility who had previously given birth failed to conceive after three frozen-thawed embryo transfer (FET) cycles. An ERA test was conducted to confirm the WOI. The first ERA test was performed 125 h after progesterone exposure. The laboratory reported that the endometrium was in a non-receptive (post-receptive) phase, and recommended retesting 101 h after progesterone exposure. A simultaneous chronic endometritis (CE) test showed a score of 3. After the antibiotics administration to treat CE, the second ERA test was performed after 101 h of progesterone exposure. The laboratory reported that the endometrium had not reached the WOI and estimated the WOI to be 113 ± 3 h after progesterone exposure. The third ERA test was performed 113 h after progesterone exposure. The laboratory reported that the endometrium was in a non-receptive (pre-receptive) phase and estimated the WOI to be 137 ± 3 h after progesterone exposure. A CE test performed at the same time as the second and third ERA tests showed a score of 1 for the collected endometrium. According to the third ERA test results, the vitrified-warmed blastocyst was transferred at 137 h of progesterone exposure. Pregnancy was achieved and the patient had an uncomplicated vaginal delivery at 39 weeks. One year later, another pregnancy was achieved after FET at 137 h of progesterone exposure, and the patient delivered at 33 weeks due to an unexpected membrane rupture. Conclusion Because the results of the ERA test may vary in the presence of CE, CE should be diagnosed simultaneously with or before conducting ERA tests. If CE is diagnosed, ERA testing should be performed after treatment with antimicrobials or other drugs.